A review of some operation and maintenance issues of CFBC boilers. (5th June 2016) - Arjunwadkar, Anand; Basu, Prabir; Acharya, Bishnu
Highlights: Detailed review of operational issues in a circulating fluidized bed boiler. Practical solutions for some of the operation and maintenance issues. Preventive maintenance procedures to predict, avoid or detect failures. Abstract: Circulating Fluidized Bed (CFB) technology has emerged as the most favoured steam generation technology in recent times. The use of CFB boilers is growing exponentially, due to its attractive features such as fuel flexibility, stable operation and low acid gas emissions, to name a few. The design of CFB boilers has developed over the years to meet the demanding availability expectations of the utilities. Proactive operation and maintenance (O&M) helps improve availability and reduce operating costs, which form a crucial component of the final steam cost of the boiler plant. This paper studies some important O&M issues of CFB boilers particularly looking into issues related to components specific to CFB boilers and the methods to avoid them. Operational difficulties like agglomeration, gas refluxing, back-sifting and performance related issues like emission control and bed temperature control are also examined. Refractory failure, which accounts for a considerable portion of the maintenance cost often forces shutdowns. This review is based on compilation of O&M issues of CFB boiler as found mainly in the open literature, but some unpublished information are also included.